Pertumbuhan Ikan Nila (Oreochromis niloticus) Dengan Pakan Buatan dengan Pakan Buatan Tepung Daun Singkong (Manihot utilissima Pohl) dan Tepung Kedelai (Glycine max) - Wardha Jalil (FPIK UNIDAYAN, 2021)
Cassava leaves (Manihot utilissima Pohl), like soybeans (Glycine max), have good nutritional to be used as raw material for alternative fish feed. The research was to determine the effect of cassava leaf flour (Manihot utilissima Pohl) and soybean (Glycine max) flour as artificial feed on the growth of tilapia (Oreochromis niloticus). It was conducted for 60 days at the Agricultural Extension Center, South Buton Regency. The organisms were gift tilapia seeds, weighing 5 – 7 grams, reared in plastic containers with a capacity of 40 liters, with a density of 10 fish/container. The feed made from cassava leaf flour, soybean flour, shrimp meal, fish meal, tapioca flour, vitamin mix, and mineral mix, was given as much as 5% of the total fish weight/day. The research design was a completely randomized design with 3 treatments and 3 replications, namely A treatment (15% cassava leaf flour and 25% soybean flour), B (25% cassava leaf flour and 15% soybean flour), C (35% cassava leaf flour and 5% soybean flour). The results showed the highest absolute growth and specific growth in B treatment (25% cassava leaf flour and 15% soybean flour) namely 17.38 ± 0.31 gram, and 2.24 ± 0.02%/day. The best FCR was 2.24 ± 0.02 in B treatment (25% cassava leaf flour and 15% soybean flour).